PENGARUH pH EKSTRAKSI TERHADAP RENDEMEN, SIFAT FISIKO-KIMIA DAN FUNGSIONAL KONSENTRAT PROTEIN KACANG GUDE (Cajanus cajan (L.) Millsp.) - Pratiwi, Hesti; Ari Yusasrini, Ni Luh; Kencana Putra, I Nengah (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2018)
The purpose of this research are to know the effect of pH extraction on yield, physico-chemical and functional properties of pigeon pea protein concentrate, and also to know the appropriate pH extraction to obtain the best yield and properties of pigeon pea protein concentrate. The research was using Randomized Complete Design with pH extraction treatment which consist of five levels were 9; 9,5; 10; 10,5; and 11. The parameters were observed consist of yield, physical properties (lightness), chemical properties (protein and moisture), and protein’s functional properties (water holding capacity, oil holding capacity, emulsion capacity and stability, and foaming capacity and stability). The result showed that pH extraction gave a significant effect to protein and moisture, and gave very significant effect to yield, lightness (L), water holding capacity, oil holding capacity, emulsion capacity, emulsion stability, foaming capacity and foaming stability of pigeon pea protein concentrate. The best properties of protein concentrate was found at sample which treatment of pH 10 with a yield 17,29% (db), lightness (L) 18,84, protein 86,15% (db), moisture 7,96% (db), water holding capacity 1,96 ml H2O/g solid, oil holding capacity 2,62 ml oil/g solid, emulsion capacity 54,67%, emulsion stability 54,83%, foaming capacity 100%, and foaming stability 38,19%.